Obturator Nerve Block for Transurethral Resection of Bladder Tumors - Aleksandra Gavrilovska Brzanov; Skender Seidi; Sotir Stavridis; Ognen Ivanovski; Josif Janchulev; Viktor Stankov; Marija Jovanovski Srceva; Biljana Kuzmanovska (COPE, 2023)
Background: Bladder tumors are identified and treated using a surgical procedure called as transurethral resection of bladder tumors (TUR-BT). During TUR-BT resection, stimulation of the obturator nerve may cause violent adductor muscle spasms. The “obturator reflex,” as this disorder is known, generally causes the legs to move inadvertently (leg jerking). Since this condition can cause several complications, it is preferable to avoid it. Objective: In this study, we investigated the effectiveness of spinal anesthesia combined with obturator nerve block or general anesthetic without muscle relaxant in preventing adductor muscle spasm during TUR-BT procedures. Methods: Forty consecutive patients were enrolled in a prospective observational evaluation and divided into two groups. Patients in Group I underwent spinal anesthesia along with an obturator nerve block, while those in Group II underwent general anesthesia without a neuromuscular relaxant. The following details were recorded: time for obturator block performance, the severity of the motor blockade, the length of the procedure in both groups because a probable adductor spasm might make it more difficult. The level of the surgeon’s pleasure was noted throughout the surgery. Additionally, the patient’s satisfaction and any issues that may have arisen were documented (the incidence of vascular puncture, hematoma, nerve damage, and visceral injury was noted). Results: Block performance time in Group I was 4.8±0.5 minutes, whereas it was 5.0±0.3 minutes in Group II. The ease of access for the two groups was the same. Group I demonstrated increased patient and surgeon satisfaction with a general anesthesia without neuromuscular relaxants and an obturatorius nerve block. Mean surgical time did not differ between the groups.There were no complications in either group. Conclusion: During such operations, routine use of ONB in combination with spinal anaesthetic or general anesthetic without a neuromuscular blocker can enhance oncological outcomes for patients, reduce complication rates, and extend the period of time spent living without disease
Keywords: obturator nerve block; transurethral resection of bladder tumor; spinal anesthesia; general anesthesia.